Assessment of point‐of‐care measurement of international normalised ratio using the CoaguChek XS Plus system in the setting of acute ischaemic stroke. Issue 11 (November 2013) - Nusa, D.; Harvey, I.; Almansouri, A. Y.; Wright, S.; Neeman, T.; Ahmad, O; Hughes, A. R.; Lueck, C. J.
Abstract Background and Aims Thrombolysis with alteplase (recombinant tissue plasminogen activator) is accepted hyperacute therapy for acute ischaemic stroke. Clotting must be normal before this can be administered safely. Laboratory testing of international normalised ratio (INR) takes 30–60 min, which can significantly delay administration of recombinant tissue plasminogen activator. Previous studies have suggested that point‐of‐care testing is useful in patients presenting with stroke and improves door‐to‐needle time. We performed a prospective study of point‐of‐care testing in patients presenting with acute ischaemic stroke. Methods Fifty patients were entered into the study to compare point‐of‐care testing using the CoaguChek XS system with laboratory testing of INR. Results Point‐of‐care testing correlated well with laboratory levels (R = 0.93, P < 0.0001). The standard deviation of difference between the two was 0.115. Overall, point‐of‐care testing tended to underestimate INR slightly, meaning that an INR value of 1.1 or less was required to be 95% certain that the laboratory value was 1.3 or below. Simultaneous testing using blood from a syringe was more consistent with laboratory results than testing capillary blood through finger prick. Conclusion Point‐of‐care INR testing correlates well with laboratory values. The results in this study mostly relate to values in the normal range. We suggest that it can be used to try to shorten door‐to‐needle time.